Resale price maintenance: a comparative study between The European Union and Malaysian Competition Laws / Mohd Safri Mohammed Na’aim - Mohammed Na’aim, Mohd Safri (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Resale Price Maintenance (hereinafter ‘RPM’) can be defined as the practice whereby a manufacturer and a distributor agree that the former will sell the latter’s products at certain prices. RPM may take a variety of forms including fixed, minimum, maximum, or recommended resale prices. In general, practice of RPM may restrict the distributors’ freedom of setting their prices at the downstream level henceforth attracting the application of competition law. The paper aims to analyse the legal status of RPM in the context of competition law in European Union and Malaysia including the ways RPM is able to restrict competition. This paper contains a detailed analysis of Article 101 of the Treaty on the Functioning of the European Union (hereinafter ‘TFEU’), the Competition Act 2010 (hereinafter ‘CA 2010’), related regulations, guidelines, case law, and scholarly writing in this area. The paper concludes that not all forms of RPM are prohibited under these two jurisdictions. Some of them are deemed illegal or anti-competitive because they are likely to harm competition and some of them may be permitted subject to the fulfilment of certain conditions.